Cost-Benefit Trade-Offs of Aquatic Resource Exploitation in the Context of Hominin Evolution - de Chevalier, Gregorio; Bouret, Sébastien; Bardo, Ameline; Simmen, Bruno; Garcia, Cécile; Prat, Sandrine (Frontiers in Ecology and Evolution, 2022)
While the exploitation of aquatic fauna and flora has been documented in several primate species to date, the evolutionary contexts and mechanisms behind the emergence of this behavior in both human and nonhuman primates remain largely overlooked. Yet, this issue is particularly important for our understanding of human evolution, as hominins represent not only the primate group with the highest degree of adaptedness to aquatic environments, but also the only group in which true coastal and maritime adaptations have evolved. As such, in the present study we review the available literature on primate foraging strategies related to the exploitation of aquatic resources and their putative associated cognitive operations. We propose that aquatic resource consumption in extant primates can be interpreted as a highly site-specific behavioral expression of a generic adaptive foraging decision-making process, emerging in sites at which the local cost-benefit trade-offs contextually favor aquatic over terrestrial foods. Within this framework, we discuss the potential impacts that the unique intensification of this behavior in hominins may have had on the evolution of the human brain and spatial ecology.